Embracing distraction. - Quek, Teng Wan. (2012)
Rapid development of Internet and technology have made researchers predicted that the most popular mental health issue will be dealing with the distraction. However, as the technology evolves, our human brains evolve at the same time. The Digital Natives are example of capable multi-taskers who can handle distraction better than the Digital Immigrants. Moreover, research has shown that people who are easily distracted are more creative than the focused counterparts. Thus, this study set out to test if embracing distraction can enhance creative process with the hypothesis that distraction can provide better creative outcomes than concentration. Personal concentration and distraction methodologies were developed and a set of 80 illustrations was produced to conduct a comparative study between concentration and distraction. The result from the comparison shows that embracing distraction enhances creative process.